Predictors of Participation in Continuing Vocational Education and Training funded by the Federal Employment Agency - Kaethe Schneider; Proskunina, Uliana (IJRDO - Journal of Social Science and Humanities Research, 2020)
The predictors of continuing vocational education and training participation are broadly investigated. Nevertheless, only few studies consider its different segments, especially the one offered by the Federal Employment Agency. We contribute to this research gap with logistic regression models on the basis of the German Socio-Economic Panel. Our analysis proves that the outcome is best predicted by the job-based characteristics, followed by the firm-based ones. Simultaneously, we find its weak dependence on the psychographic characteristics. The article provides a comprehensive review of the theoretical foundations of the investigated phenomenon as well as contributes empirically to the German adult education research